Genomic evidence for the first symbiotic Deferribacterota, a novel gut symbiont from the deep-sea hydrothermal vent shrimp Rimicaris kairei - Qi, Li; Shi, Mengke; Zhu, Fang-Chao; Lian, Chun-Ang; He, Li-Sheng (Frontiers in Microbiology, 2023)
The genus Rimicaris is the dominant organism living in hydrothermal vents. However, little research has been done on the functions of their intestinal flora. Here, we investigated the potential functions of Deferribacterota, which is dominant in the intestine of Rimicaris kairei from the Central Indian Ridge. In total, six metagenome-assembled genomes (MAGs) of Deferribacterota were obtained using the metagenomic approach. The six Deferribacterota MAGs (Def-MAGs) were clustered into a new branch in the phylogenetic tree. The six Def-MAGs were further classified into three species, including one new order and two new genera, based on the results of phylogenetic analysis, relative evolutionary divergence (RED), average nucleotide identity (ANI), average amino acid identity (AAI) and DNA–DNA hybridization (DDH) values. The results of the energy metabolism study showed that these bacteria can use a variety of carbon sources, such as glycogen, sucrose, salicin, arbutin, glucose, cellobiose, and maltose. These bacteria have a type II secretion system and effector proteins that can transport some intracellular toxins to the extracellular compartment and a type V CRISPR–Cas system that can defend against various invasions. In addition, cofactors such as biotin, riboflavin, flavin mononucleotide (FMN), and flavin adenine dinucleotide (FAD) synthesized by R. kairei gut Deferribacterota may also assist their host in surviving under extreme conditions. Taken together, the potential function of Deferribacterota in the hydrothermal R. kairei gut suggests its long-term coevolution with the host.